Electrophysiological Characterization of Regular and Burst Firing Pyramidal Neurons of the Dorsal Subiculum in an Angelman Syndrome Mouse Model - Rayi, Prudhvi Raj; Kaphzan, Hanoch (Frontiers in Cellular Neuroscience, 2021)
Angelman syndrome (AS) is a debilitating neurogenetic disorder characterized by severe developmental delay, speech impairment, gait ataxia, sleep disturbances, epilepsy, and a unique behavioral phenotype. AS is caused by a microdeletion or mutation in the maternal 15q11-q13 chromosome region containing UBE3A gene. The hippocampus is one of the important brain regions affected in AS mice leading to substantial hippocampal-dependent cognitive and behavioral deficits. Recent studies have suggested an abnormal increase in the α1-Na/K-ATPase (α1-NaKA) in AS mice as the precipitating factor leading to the hippocampal deficits. A subsequent study showed that the hippocampal-dependent behavioral deficits occur as a result of altered calcium (Ca+2) dynamics in the CA1 pyramidal neurons (PNs) caused by the elevated α1-NaKA expression levels in the AS mice. Nonetheless, a causal link between hippocampal deficits and major behavioral phenotypes in AS is still obscure. Subiculum, a region adjacent to the hippocampal CA1 is the major output source of the hippocampus and plays an important role in the transfer of information from the CA1 region to the cortical areas. In spite of the robust hippocampal deficits and several known electrophysiological alterations in multiple brain regions in AS mice, the neuronal properties of the subicular neurons were never investigated in these mice. Additionally, subicular function is also implied in many neuropsychiatric disorders such as autism, schizophrenia, Alzheimer's disease, and epilepsy that share some common features with AS. Therefore, given the importance of the subiculum in these neuropsychiatric disorders and the altered electrophysiological properties of the hippocampal CA1 PNs projecting to the subiculum, we sought to examine the subicular PNs. We performed whole-cell recordings from dorsal subiculum of both WT and AS mice and found three distinct populations of PNs based on their ability to fire bursts or single action potentials following somatic current injection: strong burst (SB), weak burst (WB), and regular firing (RF) neurons. We found no overall differences in the distribution of these different subicular PN populations among AS and WT controls. However, the different cell types showed distinct alterations in their intrinsic membrane properties. Further, none of these populations were altered in their excitatory synaptic properties.